2021
DOI: 10.1021/acs.cgd.1c00446
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Role of Structural Dynamism in Metal Organic Frameworks (MOF) for Excited-State Intramolecular Proton Transfer (ESIPT) Driven Water Sensing

Abstract: Ligand based modification has been performed to synthesize a pair of mixed ligands d10 MOF based materials related to a previously published compound as a base material. The previous compound was a Zn­(II)-MOF, {[Zn­(4-bpdh)­(H2dht)]·(MeOH)­(H2O)} n (1) [N,N′-bis­(1-pyridin-4-yl-ethylidene)­hydrazine = 4-bpdh and 2,5-dihydroxyterephthalic acid = H4dht], which is a five-fold interpenetrated framework and highly dynamic in nature. In the first synthetic modification, the central metal is replaced by Cd­(II), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…Excited intramolecular or intermolecular proton transfer is a fundamental reaction that occurs in many chemical and biochemical systems, such as a fluorescent probe, synthesis of ATP, laser dye, biological imaging, and other fields. Since Waller first reported the phenomenon of excited intramolecular proton transfer (ESIPT) of salicylic acid in the 1950s, it has attracted extensive attention because of its unique optical properties. A large amount of experimental and theoretical work focusing on the mechanism of the ESIPT process has been carried out in many systems, including quinolines, anthraquinones, flavones, and azoles, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Excited intramolecular or intermolecular proton transfer is a fundamental reaction that occurs in many chemical and biochemical systems, such as a fluorescent probe, synthesis of ATP, laser dye, biological imaging, and other fields. Since Waller first reported the phenomenon of excited intramolecular proton transfer (ESIPT) of salicylic acid in the 1950s, it has attracted extensive attention because of its unique optical properties. A large amount of experimental and theoretical work focusing on the mechanism of the ESIPT process has been carried out in many systems, including quinolines, anthraquinones, flavones, and azoles, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of well-defined broad dual emission peaks (at ∼435 and ∼615 nm) without altering their maxima throughout the measurement suggests that the present material has solid-state ESIPT behavior. Here, it is worth mentioning that our group and some others have already demonstrated that CPs with the dht ligand exhibit intriguing luminescence properties and interesting ESIPT phenomenon. However for all of them, the material needs to be in a suspension state and without any solvent used for the suspension; the material has shown only a single maximum emission behavior without any ESIPT behavior. Interestingly, for this current system, it does not need any solvent support for the ESIPT phenomenon, and to the best of our knowledge, this is the first report of solid-state ESIPT-active CP.…”
Section: Resultsmentioning
confidence: 99%
“…With intuitive design ingenuity, an appropriate ligand can be employed to construct the CP and structural modularity and can be leveraged for the structural screening to induce solid-state ESIPT phenomena. In this screening endeavor, we previously synthesized five CPs with suspension phase ESIPT behavior which is strongly influenced by the external environment; three of them 27,28 CPs. 27−29 Although there is no adequate evidence to claim that these connector systems are responsible for generalized (water and DMF to any polar solvent) solvent-dependent ESIPT phenomenon for the last two CPs; but it may have influenced the ease of proton transfer for H 4 dht.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Structural dynamism in metal organic frameworks (MOFs) is a rich topic of research in the area of material science. [1][2][3][4][5] The structurally dynamic control of porosity in MOFs, 6 which is the principal concern of many various interesting properties, [7][8][9][10] can be simply achieved by proper framework design and/or exploiting structural transformation, preferably in a single-crystal-to-single-crystal (SCSC) manner. [11][12][13] Such SCSC transformation [11][12][13] is very effective for obtaining new functional MOFs in high yield and purity, which may not be formed under conventional procedures.…”
Section: Introductionmentioning
confidence: 99%